PENGUATAN KARAKTER DAN MINAT BACA ANAK DI SDN PULO PANJANG 2 MELALUI GERAKAN LITERASI SEKOLAH BERSAMA MOTOR LITERASI (MOLI) - Desma Yuliadi Saputra; Nedi Kurnaedi; Rina Andriani; Dely Julyanti (Amal Insani Foundation, 2023)
This research aims to explore efforts to strengthen the character and reading interest of children at SDN Pulo Panjang 2 through the implementation of the School Literacy Movement in collaboration with KKM Kelompok 17 of Universitas Bina Bangsa, along with Motor Literasi (MOLI). Character education is the primary focus in shaping the moral character of students, with an emphasis on values such as responsibility, self-confidence, and appreciation. Additionally, this activity is designed to enhance children's reading interest through the integration of physical activities with literacy learning. The activity was carried out on July 29, 2023, with a total of 40 students. The methodology of this activity involved field analysis, literacy studies, and interviews. The data obtained will provide in-depth insights into how character strengthening and reading interest are integrated into the school curriculum and their impact on the moral development and reading interest of students. The results of this research are expected to provide valuable insights for other schools that are striving to integrate character strengthening and literacy to enhance the quality of moral and literacy education for children.